2008
DOI: 10.1016/j.ejon.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of nurse–patient intimacy in oncology care settings: From the nurse and patient perspective

Abstract: This paper reports the findings of a study exploring the meaning of nurse-patient intimacy in oncology care settings. An interpretive phenomenological design was adopted. A total of 23 oncology nurses and 30 oncology patients, from 3 hospitals, were interviewed between March 2005 and December 2005. Three main themes emerged from the data: developing intimacy, experiencing intimacy and outcome of intimacy. Nurse-patient intimacy is revealed as a process, which begins when the nurse and patient first meet, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 53 publications
(76 reference statements)
5
41
0
8
Order By: Relevance
“…Also, Dowling found that nurses' technical skills were alluded to by both nurses and patients interviewed as a contributing factor to the closeness of their relationship. When the patient trusted the nurse's competence with regard to their technical skills, they wanted that nurse to care for them [28]. In a recent theoretical account on caring, researcher supported the notion that helping patients with big (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Dowling found that nurses' technical skills were alluded to by both nurses and patients interviewed as a contributing factor to the closeness of their relationship. When the patient trusted the nurse's competence with regard to their technical skills, they wanted that nurse to care for them [28]. In a recent theoretical account on caring, researcher supported the notion that helping patients with big (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, research conducted with people from Europe, the Middle East, Africa, and the USA has all found that patients describe good patient-nurse relationships as encompassing trust, emotional support and being treated as an individual and as allowing them to feel secure enough to depend on and share their fears with the nurse (Ramos 1992, P alsson & Norberg 1995, Deeny & McGuigan 1999, Coffey 2006, Dowling 2008, Rchaidia et al 2009, Beaver et al 2010, Kristiansen et al 2010, Remmers et al 2010. If the nursepatient relationship has characteristics of an attachment relationship, we should expect that patients' attachment models would influence their experience of the relationship.…”
Section: Nurses As Attachment Figures?mentioning
confidence: 98%
“…A number of authors have discussed that oncology nurses are motivated by sustaining relationships that they develop with patients and their families (Berterö, 1999;Dowling, 2008). To develop effective training programs, having a complete understanding of what prompts experienced nurses to continue working in oncology and recognizing how oncology nursing differs from other specialty areas are vital.…”
mentioning
confidence: 99%